Poverty and food insecurity could grow dramatically as COVID-19 spreads - Laborde Debucquet, David; Martin, Will; Vos, Rob (International Food Policy Research Institute, 2020)
With COVID-19 and its economic fallout now spreading in the poorest parts of the world, many more people will become poor and food-insecure. In a new scenario analysis, we estimate that globally, absent interventions, over 140 million people could fall into extreme poverty (measured against the $1.90 poverty line) in 2020 — an increase of 20% from present levels. This in turn would drive up food insecurity. A global health crisis could thus cause a major food crisis — unless steps are taken to provide unprecedented economic emergency relief.